PEMANFAATAN DAUN DALUMAN MENJADI MINUMAN CAPCIN CAU SEBAGAI PRUDUK KULINER UMKM KABUPATEN BANYUWANGI - Handoko, Rudi Tri; Hariani, Indah Kurnia; Mecha, I Putu Sudhyana (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2024)
Capcin Cau (Capcin Cau) is a coffee variant drink with cincau filling made from daluman leaves. The processing of Capcin cau culinary products is very easy and the nutritional content of daluman leaves which are good for health has led to innovative ideas for beverage processing for UMKM in Banyuwangi. The purpose of this study is to utilize daluman leaves as a culinary product that can generate high selling points and create new product innovation ideas for UMKM in Banyuwangi.Seeing this potential, an experiment was carried out using daluman leaves to make cappuccino cincau drinks. This study used a non-factorial randomized block design with organoleptic tests including hedonic quality tests and hedonic tests. The best treatment from the results of the Hedonic Quality Test was T1 with a score of 4.20 and the best treatment in the Hedonic Test was T1 with a score of 4.46. After the organoleptic testing was carried out, it was followed by analyzing the selling prices of these UMKM culinary products so that they could be known and enjoyed by the public.